2020
DOI: 10.3390/app10041235
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Pipeline to Obtain 3D Model for HBIM and Structural Analysis Purposes from 3D Point Clouds

Abstract: The aim of this work is to identify an efficient pipeline in order to build HBIM (heritage building information modelling) and create digital models to be used in structural analysis. To build accurate 3D models it is first necessary to perform a geomatics survey. This means performing a survey with active or passive sensors and, subsequently, accomplishing adequate post-processing of the data. In this way, it is possible to obtain a 3D point cloud of the structure under investigation. The next step, known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 17 publications
0
67
0
2
Order By: Relevance
“…The dense point cloud of the coast was obtained using 3DF Zephyr Aerial software (Pepe et al, 2020); in this way, it was possible to generate three-dimensional models from the acquired images ( Fig. 7).…”
Section: Post-processing Of the Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dense point cloud of the coast was obtained using 3DF Zephyr Aerial software (Pepe et al, 2020); in this way, it was possible to generate three-dimensional models from the acquired images ( Fig. 7).…”
Section: Post-processing Of the Imagesmentioning
confidence: 99%
“…The precision achieved on photogrammetric model was about 0.08 metres and the accuracy around 0.10 metres. The high number of photos (more than 50) in the project, the high geometric resolution, the high quality of the images and the high coverage of the images have allowed obtaining a very detailed and dense cloud point (over 7 million points) of the study area; more details can be found on (Pepe et al, 2020). Starting from the georeferenced point cloud, the mesh and, subsequently, the colour orthophoto with a spatial resolution of 0.02 metres were generated.…”
Section: Post-processing Of the Imagesmentioning
confidence: 99%
“…The modeling phase is the last and most challenging stage. The literature presents several different strategies for building BIM models [ 38 , 39 , 40 ]. Two main working methods used to build 3D models are direct and parametric modelling [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, from the point cloud, it is possible to build, in Rhinoceros environment, a detailed model of every single element. The construction of the objects was made possible by creating special profiles directly on the point cloud thanks to the use of Arena 4D tool [14]. For example, a vector representation of the point cloud during the construction phase is shown below (Fig.…”
Section: Building Of the Geometries Of The Single Elements Of The Bridgementioning
confidence: 99%
“…Kaimaris et al [13] discussed the use of UAV photogrammetry and SfM-MVS approaches in order to locate and map the Traces of the Covered Ancient Theater of Amphipolis (Eastern Macedonia, Greece), which is one of the most important archaeological sites of Greece. Pepe et al [14] discussed the construction of a three-dimensional model involving a photogrammetric method applied to a Roman bridge (called Ponte san Cono) for structural analysis purposes; in this latter study, the building of 3D models using FEM (Finite Element Method), a novel approach that uses Rhinoceros software to 3D reconstruction of the bridge, is discussed. Starting from this study, we suggest an original method for the survey involving UAV and, once the 3D model has been realized, a suitable procedure for the maintenance and computer management of the structure has been identified.…”
Section: Introductionmentioning
confidence: 99%